TANGGUNG JAWAB NEGARA TERHADAP PERLINDUNGAN DATA PRIBADI DI INDONESIA DALAM PERSPEKTIF HAK ASASI MANUSIA - Eric Ardiansyah Pery; Emilda Firdaus; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The 1945 Constitusion of the Republic of Indonesia Article 28G stipulates that a personhas the right to project himself, family, honor, dignity, and wealth as well as a sense of securityfrom all forms of the threats that exist from his possession. And in Law No.30 of 1999concerning Human Right, Article 29 Everyone has the right to protection of personal, family,honor, dignity and property right. And in Article 32 of Law Number 39 Year 1999, it is explainedthat independence and confidentiality in correspondence, including communication by electronicmeans, cannot be disturbed, except by order of a judge or other legal outhority in accordancewith the provisions of the legislation.This research will be compiled using the juridical normative research type, which isresearch focused on examining the application of the norm of positive law. The approach used inthis research is to use a normative approach, namely literature law research.The results of the research conducted by the outhor are, first, to find out how theprotection of the law and the responsibility of the State for the protection of personal data inIndonesia in the context of protecting human rights and to obtain the right to protect personaldata for the public is part of the implementation of protecting human right. Furthermore, inorder to know the ideal concept of personal data protection, citizens have the right to obtainpersonal data protection information.Keywords: State Responsibility - Personal Data Protection